Reflections on the history of the Kaliningrad region - Galtsov V. I. (Слово.ру: балтийский акцент, 2017)
This article describes differences and contradictions in identifying the subject of Kaliningrad regional history. Some researchers and media interpret the term ‘Kaliningrad regional history’ as the history of the region per se and others as the whole scope of local history. The ‘History of West Russia: The Kaliningrad Region’, a secondary school discipline taught since 2006, presents an interesting case. The subject of the Kaliningrad regional history has no single definition since it is a matter of politics rather than historiography. The inability to produce such a definition stems from the uniqueness of the region’s geographical position and history. The region’s history was used extensively in the Soviet time for political and ideological purposes. The current confrontation between Russia and the West lends new urgency to the problem of teaching local history, ninety percent of which is the history of a territory that once belonged to Germany — today, a pillar of the EU and a member of NATO. The author examines whether it is reasonable to draw on international experience in patriotic education. The subject ‘History of West Russia: The Kaliningrad Region’ was taken off the school timetable. The article stresses the need to teach a course on East Prussian history and proposes to treat it as the regional aspect of universal history.